The Far planets - Time-Life Books (Alexandria, Va. : Time-Life Books, 1988)
Examines what is known about the five outer planets.
Includes index.
Bibliography: p. 139-140.
8.9
8.9
7-10.
Young Adult
Keywords: Outer planets; Planets